RESPONS SISWA TERHADAP KUIS GAMIFIKASI BLOOKET PADA PEMBELAJARAN IPS KELAS VIII PEMINATAN OLIMPIADE - Anna Putry, Shanty; Bachri, Syamsul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Social Studies instruction in the Olympiad-track class presents different challenges compared to other specialized classes. Based on initial observations, Social Studies lessons in the class felt rigid and lacked vitality. Although the students were compliant, completed their assignments well, and participated in the lessons in a positive manner, The classroom atmosphere felt lacking in enthusiasm, monotonous, and characterized by low emotional engagement. The purpose of this study is to describe students’ responses to the implementation of gamified quizzes in social studies instruction in an 8th-grade Olympiad-track class and to identify the obstacles that arise during implementation. This study employs a descriptive quantitative approach using a one-shot case study design. The research subjects consisted of 30 eighth-grade students. Data were collected through a questionnaire using a four-point Likert scale covering the following response aspects: cognitive, affective, conative, and technical. The results show that student responses to the use of gamified quizzes in social studies instruction in the Olympiad-track class were 85.6% for the cognitive aspect, 86.5% for the affective aspect, and 82.7% for the conative aspect. However, the technical aspect only reached 60%, which falls into the “fair” category. This was due to network issues and lag experienced by some students. Overall, the average score across all these aspects fell into the “positive” category, with a percentage of 78.8%. The findings of this study indicate that Blooket gamified quizzes have the potential to serve as a more effective and enjoyable medium for social studies learning; however, attention must be paid to network connectivity and the selection of appropriate game modes. This study contributes to gamification strategies in highly competitive classrooms and highlights the importance of technical aspects in the implementation of digital game-based learning.